Immunomodulatory Effect of Irreversible Electroporation Alone and Its Cooperating With Immunotherapy in Pancreatic Cancer - Tian, Guo; Guan, Jiajia; Chu, Yanhua; Zhao, Qiyu; Jiang, Tian’an (Frontiers in Oncology, 2021)
Emerging studies have showed irreversible electroporation (IRE) focused on pancreatic cancer (PC). But the effects of IRE treatment on the immune response of PC remain unknown. Moreover, there are few studies on the therapeutic effect of IRE combining with immunotherapy on PC. Thus we review recent advances in our understanding of IRE alone and its working with immunotherapy towards the immune response of PC, discussing potential opportunities for exploring future treatment strategies.